The Ways to Optimize Mobile Phone Usage in English Instructional Activities - Nur Fadillah Nurchalis; Nurzamzam Nurzamzam (Journal of English Language Studies, 2023)
In the midst of controversial perceptions among students and teachers regarding the use of mobile phone in the classrooms, it is urgent to look for solution in order that these sophisticated devices are able to bring more benefits in language learning. This research aims at exploring students’ and teachers’ perceptions on how to optimize the mobile phones in English instructional activities so that the teaching and learning can be attractive and interactive, hence students’ participation in the classroom may increase as well as their learning outcome. This research applied qualitative research. The informants participated in this research were two English teachers and four students from two state Islamic senior high schools in Parepare, Indonesia. To collect the data, the researchers employed Focus Group Discussion (FGD). Students and teachers sat together in a forum to discuss and to argue their opinion or experiences in order that the use of mobile phones in the classroom during English learning activities can be optimal. To analyze the data, the researchers analyzed them by using thematic technique from Creswell. The results of this research show that there were five ways offered by both students and English teachers. Those ways are recommended to apply by both parties without too much worry because of potential distractions that may come up.